2023
DOI: 10.1007/s11912-022-01352-7
|View full text |Cite
|
Sign up to set email alerts
|

The Microbiome’s Influence on Head and Neck Cancers

Abstract: Purpose of Review Head and neck tumors (HNC) rank sixth among cancers worldwide. Due to their late diagnosis and poor prognosis, they are a clinical challenge. However, recent years have seen a dynamic development of science on the microbiome. The aim of the study is to discuss the role of the microbiome in HNC, the impact of the microbiome on oncogenesis, the course of the disease, as well as on treatment, and its toxicity. Recent Findings The microbiome’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 104 publications
1
12
0
Order By: Relevance
“…It is estimated that the 5-year survival rate is less than 50% ( Dorobisz et al., 2023 ). Human papilloma virus (HPV) (especially type 16), Epstein–Barr virus, tobacco, usage of alcohol, and poor oral hygiene are the main risk factors of head and neck cancer (HNC) ( Hübbers and Akgül, 2015 ; Rettig and D’Souza, 2015 ; Cohen et al., 2018 ; Kaidar-Person et al., 2018 ; Dorobisz et al., 2023 ). It is estimated that even 4.5% of cancers worldwide are associated with HPV infection ( Roman and Aragones, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is estimated that the 5-year survival rate is less than 50% ( Dorobisz et al., 2023 ). Human papilloma virus (HPV) (especially type 16), Epstein–Barr virus, tobacco, usage of alcohol, and poor oral hygiene are the main risk factors of head and neck cancer (HNC) ( Hübbers and Akgül, 2015 ; Rettig and D’Souza, 2015 ; Cohen et al., 2018 ; Kaidar-Person et al., 2018 ; Dorobisz et al., 2023 ). It is estimated that even 4.5% of cancers worldwide are associated with HPV infection ( Roman and Aragones, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that even 4.5% of cancers worldwide are associated with HPV infection ( Roman and Aragones, 2021 ). The difference of the overall microbiome (not only viral infections) profile between healthy people and patients with HNCs was detected ( Dorobisz et al., 2023 ). In the study of Hayes et al., it was shown that abundance of oral microbes, such as Corynebacterium and Kingella , is related to a lower risk of HNSCC ( Hayes et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…HNCs have a multifactorial etiology, including genetic and epigenetic mechanisms ( 3 ), oral dysbiosis ( 4 ), infections with human papilloma virus (HPV), mostly oncogenic types 16 and 18 ( 5 ), and EBV (Epstein-Barr virus) ( 6 ), laryngopharyngeal reflux ( 7 ), prior exposure to radiotherapy ( 8 ) as well as various lifestyle features, such as heavy smoking and alcohol consumption ( 9 , 10 ), chewing betel quid (Areca nuts) ( 11 ), marijuana use ( 12 ), poor oral hygiene ( 13 , 14 ), pro-inflammatory diet (e.g., fried, smoked, or roasted meat) ( 15 ), oral dysbiosis ( 16 ), prolonged exposure to sunlight, inhalation of chemical pollutants ( 17 22 ) ( Figure 1 ). These multifaceted risk factors highlight the need for comprehensive strategies in both prevention and management to combat HNCs effectively.…”
Section: Introductionmentioning
confidence: 99%
“…Several papers recently described the role of HPV infection and the composition of the host microbiome in HNCs carcinogenesis ( 4 , 28 , 32 35 ). However, there is still a lack of understanding of the association between human microbiota signatures and the risk of HNCs, designating new biomarkers in HNCs diagnosis, and the implication of dysbiosis in HNCs therapy.…”
Section: Introductionmentioning
confidence: 99%